MEMAHAMI NIAT ANGGOTA KOPERASI (Studi Pada Koperasi Taman Usaha Jepara) - Novita Wulandari, 13.05.51.0233; Santoso, Eric (Students' Journal of Economic and Management, 2018)
This study aims to understand and analyze members' intentions at the Cooperative Taman Usaha in Jepara City. The population in this study is a member of Cooperative Taman Usaha. Sampling technique using purposive sampling with criteria of respondents who have become members of the cooperative. The sample in this study was obtained as 115 respondents. Data analysis method used include, descriptive statistics, instrument test include validity test with KMO value >0.5 and loading factor >0,4 and reliability test with alpha cronbach >0,7, model advisability test include F test and coefficient of determination test , and hypothesis test with significance <0,05. Based on the results of hypothesis test results obtained: Attitudes have a positive and significant effect on the intention of being a member of Cooperative Taman Usaha. Subjective Norm have a positive and significant effect on the intention of being a member of Cooperative Taman Usaha. Perceived Behavior Control have a positive and significant effect on the intention of being a member of Cooperative Taman Usaha.Keywords: Attitude, Subjective Norms, Perceived Behavioural Control, Intention